Rekonstruksi Epistemologi Islam: Kajian Filsafat Ilmu terhadap Pemikiran Mohammed Arkoun - Khairunnisa, Khairunnisa; Warni, Indah; Julita, Julita; Burhan, Wahyuni Syafitri; Siregar, Pahri (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: This studi aimed to analyze the reconstruction of Islamic epistemology in the thought of Mohammed Arkoun with a particular emphasis on its axiological dimension. The study departs from the assumption that the crisis of contemporary Islamic thought is not merely methodological in nature but is also related to the value orientation (axiology) underlying the production of religious knowledge. This research employs a qualitative approach based on library research, combined with a philosophical-critical analysis of Arkoun’s major works, particularly those related to the concepts of Critique of Islamic Reason, unthought, and Islamology Applied. The findings reveal that the epistemological reconstruction proposed by Arkoun does not merely aim to deconstruct the orthodoxy of Islamic scholarship but also shifts the value orientation of Islamic studies from a doctrinal-transmissive model toward a more humanistic, reflective, and dialogical production of meaning. From an axiological perspective, Arkoun’s ideas emphasize the importance of liberating reason from the sacralization of interpretative products, strengthening epistemic plurality, and integrating the social sciences and humanities into Islamic studies. The implications of these findings suggest that the reconstruction of Islamic epistemology should be directed toward strengthening scholarly ethics, intellectual openness, and social relevance in responding to the challenges of modernity. Thus, the contribution of this article lies in affirming that the renewal of Islamic studies involves not only methodological innovation but also the reformulation of value orientations that shape the purpose and function of knowledge in contemporary Muslim civilization.Keywords: Islamic epistemology, axiology, Mohammed Arkoun, philosophy of science. Abstrak: Studi ini bertujuan menganalisis rekonstruksi epistemologi Islam dalam pemikiran Mohammed Arkoun dengan menitikberatkan pada dimensi aksiologisnya. Studi ini berangkat dari asumsi bahwa krisis pemikiran Islam kontemporer tidak hanya bersifat metodologis, tetapi juga berkaitan dengan orientasi nilai (aksiologi) yang mendasari produksi pengetahuan keagamaan. Penelitian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan (library research) dengan analisis filosofis-kritis terhadap karya-karya utama Arkoun, khususnya terkait konsep Critique of Islamic Reason, unthought, dan Islamology Applied. Hasil kajian menunjukkan bahwa rekonstruksi epistemologi yang ditawarkan Arkoun tidak semata bertujuan mendekonstruksi ortodoksi keilmuan Islam, melainkan menggeser orientasi nilai studi Islam dari model transmisi-doktrinal menuju produksi makna yang humanistik, reflektif, dan dialogis. Secara aksiologis, gagasan Arkoun menegaskan pentingnya pembebasan nalar dari sakralisasi produk tafsir, penguatan pluralitas epistemik, serta integrasi ilmu-ilmu sosial-humaniora dalam studi Islam. Implikasi temuan ini menunjukkan bahwa rekonstruksi epistemologi Islam harus diarahkan pada penguatan etika keilmuan, keterbukaan intelektual, dan relevansi sosial dalam menjawab tantangan modernitas. Dengan demikian, kontribusi artikel ini terletak pada penegasan bahwa pembaruan studi Islam tidak hanya menyangkut aspek metodologi, tetapi juga orientasi nilai yang membentuk tujuan dan fungsi ilmu dalam peradaban Muslim kontemporer.Kata kunci: Epistemologi Islam, Aksiologi, Mohammed Arkoun, Filsafat Ilmu.